Transformation of Islamic Religious Education Learning from Conventional to Interactive: A Case Study of SMPN 35 Surabaya - Firdanti Maqhfiroh; Moh. Faizin; Usman Yudi; Yahya Aziz (al-Afkar, Journal For Islamic Studies, 2026)
The purpose of this study is to describe the transformation of Islamic Religious Education (PAI) learning from conventional methods to interactive methods for class VIII-F students at SMPN 35 Surabaya. The research method used is a qualitative descriptive approach involving 33 students as subjects, while data was collected through three main techniques: observation, interviews, and documentation. The results of the study indicate that conventional learning, which is still dominated by lectures, memorization, and cognitive evaluation alone, causes students to tend to be passive, bored, and fed up. In contrast, the implementation of conventional learning through LKPD-based Problem Based Learning (PBL), mind mapping-based Project Based Learning (PjBL), and Kahoot-based digital game evaluation can increase student engagement, motivation, and deeper understanding. Students become more active in discussions, collaboration, and problem-solving, while the teacher acts as a facilitator. This study concludes that the integration of interactive learning with the Independent Curriculum is relevant for building Islamic Religious Education (PAI) learning that is more participatory, meaningful, and aligned with the demands of 21st-century skills.